(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Generation Z refers to those born between 1996 and 2010. Generation Z is entering the workforce and becoming the leading consumer market force. Studying the consumption intentions of Generation Z toward domestic sports brand apparel can significantly benefit the brand’s future business development. This study employs a questionnaire survey and incorporates factors from the Technology Acceptance Model (TAM) based on the Theory of Planned Behavior (TPB) to investigate the factors influencing Generation Z consumers’ online purchasing intentions for Chinese sports brand apparel. The results indicate that the behavioral intentions of Generation Z towards domestic sports brands are significantly positively correlated with subjective norms, perceived behavioral norms, usefulness, and ease of use.